Digitalization Model for MSME Sales in Rural Areas: A Case Study of OpenCart Integration with Social Media - Ihdi Syahputra; Desriana; Rani Kusniati (BALQIS : Journal of Business Innovation and Digital Marketing, 2025)
Small businesses in Koto Balingka sub-district face major challenges in marketing and selling chip products, especially in the increasingly competitive digital market. The aim of this research is to create a promotional and sales strategy that integrates the OpenCart platform into social media to increase market reach and operational effectiveness. Interviews with local businesses were used to collect data. View sales and conventional procedures reducing the need for business digitalization. The OpenCart system was chosen for its moment, ease of use, and integration with various social media platforms such as Facebook and Instagram. Business owners can manage product catalogues, orders, and promotions quickly with this integration. Implementation results show that promotional effectiveness and consumer affordability have increased. Digital marketing methods, which include the implementation of paid advertising and interactive content, succeeded in increasing online store visits by up to forty percent in the first three months of implementation. This study found that combining the OpenCart platform with social media platforms could be a useful model for building small businesses in rural areas. This system not only helps business owners, but also offers opportunities for collaboration with new business partners. Additional research should look at how implementing these systems impacts the profitability of small businesses in various industries.   Pelaku usaha kecil di kecamatan Koto Balingka menghadapi tantangan utama dalam pemasaran dan penjualan produk keripik, terutama di pasar digital yang menjadi lebih kompetitif. Tujuan dari studi ini adalah untuk membuat strategi promosi dan penjualan yang mengintegrasikan platform OpenCart ke media sosial untuk meningkatkan pasar jengkauan dan efektivitas operasional. Wawancara dengan bisnis lokal digunakan untuk mengumpulkan data. Lihat prosedur penjualan dan konvensional mengurangi kebutuhan digitalisasi bisnis. Sistem OpenCart dipilih karena momennya, kemudahan penggunaan, dan integrasinya dengan berbagai situs media sosial, termasuk Facebook dan Instagram. Pemilik usaha dapat mengelola katalog produk, pesanan, dan promosi secara singkat dengan integrasi ini. Hasil implementasi menunjukkan bahwa efektivitas promosi dan keterjangkauan konsumen meningkat. Metode pemasaran digital yang mencakup penerapan iklan berbayar dan konten interaktif, berhasil meningkatkan kunjungan toko online hingga empat puluh persen dalam tiga bulan pertama implementasi. Studi ini menemukan bahwa penggabungan platform OpenCart dengan platform media sosial dapat menjadi model yang berguna untuk membangun bisnis kecil di wilayah rarul. Sistem ini tidak hanya membantu pemilik usaha, tetapi juga menawarkan peluang untuk kaloborasi dengan mitra bisnis baru. Penelitian tambahan harus melihat bagaimana penerapan sistem ini berdampak pada profitabilitas usaha kecil di berbagai industri